1994
DOI: 10.1007/bf00269353
|View full text |Cite
|
Sign up to set email alerts
|

CD44 variant isoforms are preferentially expressed in basal epithelia of non-malignant human fetal and adult tissues

Abstract: CD44 is a transmembrane glycoprotein, which can exist in a multitude of isoforms due to alternative splicing of the pre-mRNA. We have generated monoclonal antibodies to several of these variant regions, which are encoded by 10 additional exons in the extracellular part of the molecule. CD44 variant isoforms have been reported to be involved in the malignant progression of rat and human tumours. The precise localization of CD44 variant isoforms in normal developmental and morphogenetic processes is essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
66
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 27 publications
10
66
1
1
Order By: Relevance
“…Our observation that PROMININ-2 is predominantly expressed in the basal cells of the human prostatic epithelium is in line with the diVerential gene expression observed between cells morphologically segregated into basal and luminal compartments (Terpe et al 1994;Signoretti et al 2000;Tokar et al 2005). Although not free from controversies, several observations indicate that basal and secretory cells are hierarchically related, where basal cells represent (or include) the progenitors for terminally diVerentiated luminal ones implying that the adult stem cells responsible for homeostatic replacement reside in the basal compartment (Aumüller 1991;BonkhoV and Remberger, 1996;Robinson et al 1998;Signoretti et al 2005;Signoretti and Loda 2006).…”
Section: Discussionsupporting
confidence: 86%
“…Our observation that PROMININ-2 is predominantly expressed in the basal cells of the human prostatic epithelium is in line with the diVerential gene expression observed between cells morphologically segregated into basal and luminal compartments (Terpe et al 1994;Signoretti et al 2000;Tokar et al 2005). Although not free from controversies, several observations indicate that basal and secretory cells are hierarchically related, where basal cells represent (or include) the progenitors for terminally diVerentiated luminal ones implying that the adult stem cells responsible for homeostatic replacement reside in the basal compartment (Aumüller 1991;BonkhoV and Remberger, 1996;Robinson et al 1998;Signoretti et al 2005;Signoretti and Loda 2006).…”
Section: Discussionsupporting
confidence: 86%
“…CD44, a hyaluronate receptor, is involved in cell migration through the ECM, which can be viewed as highly relevant for tumour invasion and metastasis. Previous studies have indicated that CD44 isoform expression may be related to gastric tumour progression and poor prognosis for the patient Mayer et al, 1993;Mulder et al, 1994;Terpe et al, 1994;Günthert et al, 1995). Given the fact that progression of tumours is modulated by changes in cell -cell interactions of the progressing tumour clones, we especially focused on the expression of Ep-CAM, an epithelial cell adhesion molecule, involved in regulation of cadherin adhesions, and, possibly, cell proliferation and invasion (Litvinov et al, 1994a, b;Litvinov, 1995).…”
mentioning
confidence: 99%
“…lymphomas, renal cell tumors and colon carcinomas (Stauder et al, 1995a;Tanabe and Saya, 1994). While many tumors show a positive correlation between tumor progression and expression of CD44v Terpe et al, 1994;Wielenga et al, 1993), neuroblastomas, highly malignant tumors derived from the neuronal crest, exhibit an inverse correlation between CD44S expression and tumor progression (Christiansen et al, 1995b;Combaret et al, 1995;Shtivelman and Bishop, 1991).…”
Section: Introductionmentioning
confidence: 99%